2001
DOI: 10.1111/j.1744-7976.2001.tb00290.x
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Agricultural Trade Impact of Spain's Integration into the EU

Abstract: The aim of this paper is to provide an econometric framework from which to assess the impact on Spanish agricultural trade by the entry of Spain into the European Union. This framework is based on the estimation of a gravity equation. Special attention is paid to the inclusion of dynamics in the gravity equation. To do that, the Kalman filter is used to define the antimonde, that is, the hypothetical situation that would exist without the integration of Spain into the EU. Results show that although Spain joine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
4
6
0
1
Order By: Relevance
“…In our case, new empirical evidence is gathered of the positive effect of integration into the EU, from a very long-term perspective and in a disaggregated fashion for the distinct subsectors which comprise the food and drink industry. These results complement the academic debate which has focused solely on the effect of the liberalisation of the barriers to trade with Spanish incorporation into the EU (Contreras & Bacaria, 2000;Sanz, 2000;Sanz & Gil, 2001;Gil Pareja et al, 2005;Selva & Álvarez-Coque, 2011). In addition, we can partially qualify the results of some previous studies, since the positive effect upon the exports of the Spanish agrifood industry as a consequence of the liberalisation of the EU markets occurred later than the actual date of adherence.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In our case, new empirical evidence is gathered of the positive effect of integration into the EU, from a very long-term perspective and in a disaggregated fashion for the distinct subsectors which comprise the food and drink industry. These results complement the academic debate which has focused solely on the effect of the liberalisation of the barriers to trade with Spanish incorporation into the EU (Contreras & Bacaria, 2000;Sanz, 2000;Sanz & Gil, 2001;Gil Pareja et al, 2005;Selva & Álvarez-Coque, 2011). In addition, we can partially qualify the results of some previous studies, since the positive effect upon the exports of the Spanish agrifood industry as a consequence of the liberalisation of the EU markets occurred later than the actual date of adherence.…”
Section: Discussionsupporting
confidence: 55%
“…For the Spanish agrifood sector, however, research in this line has been very limited in comparison to studies focusing on other effects such as the liberalisation of trade barriers. The focus has been on Spanish incorporation into the EU, paying little attention to other factors which also favour the expansion of such trade (Contreras & Bacaria, 2000;Sanz, 2000;Sanz & Gil, 2001;Gil Pareja et al, 2005;Selva & Álvarez-Coque, 2011) and thus studies of this factor are needed. We also believe that analysing the food trade from this other perspective is important, as this is crucial to an understanding of Spanish exports.…”
Section: Data Collectionmentioning
confidence: 99%
“…Other than theoretical studies cited above there have been some studies attempting to establish the theoretical foundations of such models (Eaton & Kortum, 1997; Helpman & Krugman, 1985). On the other hand, some other studies have examined agricultural trade flow (Atici & Guloglu, 2006; Atici & Furuya, 2008; Cho, Sheldon, & McCorriston, 2002; Furtan & van Melle, 2004; Sanz & Gil, 2001).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Brada and Mendez (1983), on the other hand, found that the population of home and partner countries had a positive impact on trade flow. In addition, a study examining the agricultural trade flow from Spain to the EU (Sanz & Gil, 2001), and another study examining the agricultural trade flow in ASEAN (Association of South East Asian Nations) members (Atici & Furuya, 2008), found that the population of home and partner countries has a positive impact on the flow of agricultural exports. The distance between two partners determines the transportation cost and negatively affects the trade flow.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Brada and Mendez 7 , on the other hand, found that the population of home and partner countries' had a positive impact on trade flow. In addition, a study examining agricultural trade flow from Spain to the EU 26 found that the populations of reporter and partner countries have a positive impact on agricultural export flow. The dummy variable of being an ASEAN member may have an ambiguous sign.…”
Section: The Modelmentioning
confidence: 99%